Average Vector Field Splitting Method for Nonlinear Schrodinger Equation - Akkoyunlu, Canan; Karasözen, Bülent (Springer-Verlag Berlin, Heidelberger Platz 3, D-14197 Berlin, Germany, 2013)
The energy preserving average vector field integrator is applied to one and two dimensional Schrodinger equations with symmetric split-step method. The numerical results confirm the long-term preservation of the Hamiltonians, which is essential in simulating periodic waves.
Keywords: Physics, Mathematical